Orofacial granulomatosis - Srinivas Kandula; Atul A Bajoria; Sangamesh N Chinnannavar; Ashok Lingappa (Wolters Kluwer Medknow Publications, 2016)
Orofacial granulomatosis (OFG) is a rare disease, usually presenting as a persistent swelling of the soft tissues in the orofacial region, predominantly lips (cheilitis granulomatosa). The treatment of OFG can be challenging as frequent recurrences are very common. Here, we present a case of an Asian female patient with persistent swelling of the upper lip from the past 6 months. After establishing the diagnosis, intralesional triamcinolone injection (10 mg on a weekly schedule) was planned for a period of 6 weeks. Complete resolution of the lesion was observed. This article presents a unique case of cheilitis granulomatosa (CG) with a brief highlight on the various treatment modalities and a structured algorithm discussing the various differential diagnoses, aiding in formulating an accurate diagnosis and effective treatment.